Hi, I had this sum for an exam and I couldn't get it, so I just wanted to know how to solve it:
Given: sinA + sin^2A = 1
Calculate: cos^12A + 3cos^10A + 3cos^8A cos^6A 2cos^4A 2cos^2A - 2
I didn't know how to use the code, so I used ^ for power. Sorry for that.
This is what I did:
sinA + sin^2A = 1
sinA = 1 - sin^2A
But, 1 - sin^2A = cos^2A
Therefore, sinA = cos^2A
...And then I substituted cos^2A as sinA throughout this:
cos^12A + 3cos^10A + 3cos^8A cos^6A 2cos^4A 2cos^2A - 2
Yet, I could not arrive at an answer. All help is greatly appreciated.
Thanks,
RoH.